Influence of nappe structure on the Carboniferous volcanic reservoir in the middle of the Hongche Fault Zone, Junggar Basin, China - Chen Zhengyu; Qin Qirong; Li Hu; Zhou Jiling; Wang Jie (Open Geosciences, 2023)
This work presents an in-depth examination of the Carboniferous volcanic reservoir within the CH471 well area, situated in the central portion of the Hongche fault zone on the northwestern margin of the Junggar Basin. Leveraging seismic data and well connection comparisons, we scrutinize the tectonic evolution model and elucidate the impact of the nappe structure of the Hongche fault zone on the volcanic reservoir. The study has obtained the following understanding: after the formation of Carboniferous volcanic rocks, affected by the Hongche fault structure, a series of structural superpositions from extension to extrusion and finally thrust occurred, resulting in a northwestward tilt of the volcanic rock mass, and a large number of cracks were generated inside the rock mass. At the same time, the top was uplifted and affected by weathering and leaching to form a weathering crust, eventually forming a reservoir. The northern part is located in the edge area of the eruption center, and the rock mass has good stratification. The rock strata have certain constraints on the reservoir distribution, and the reservoir is inclined along the rock mass. The southern part is close to the eruption center and features large volcanic breccia accumulation bodies with strong internal heterogeneity. The reservoir developed mainly in the superposition of the range of control of the weathering crust and dense fracture development, and the rock mass morphology does not control the area. Structure is the key to forming a volcanic rock reservoir, mainly reflected in the following aspects. First, tectonic activity is accompanied by fracture development, and fractures are densely developed in areas with strong activity, which can effectively improve the physical properties of volcanic reservoirs. Second, tectonic activity leads to the strata uplift and weathering denudation, forming a weathering crust. Within the range of control of weathering and leaching, the physical properties of volcanic rocks are improved, and it is easier to form high-quality reservoirs. Third, the distribution of volcanic rock masses is controlled by tectonic activity, which affects the reservoir controlled by the dominant lithology.